Membangun Kualitas Kepenulisan Ilmiah melalui Pelatihan Penulisan Artikel Ilmiah para Mahasiswa di STIT Al-Washliyah Binjai - Purba, Abdur Rahman; Yusuf Siregar , Muhammad; Suwandi, Suwandi; Pardi, M. Habib Husnial (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2024)
Education scientific writing is a 21st century learning whose application is rarely found in high schools in Indonesia at the beginning of the semester. This community service program at the Tarbiyah Al-Washliyah College of Science aims to improve the skills and confidence of new students in scientific writing. This education-based peer mentoring development service was carried out at Al-Washliyah Binjai Tarbiyah High School with the involvement of nearly 90 new students as partner subjects. Through a series of workshops and mentoring sessions, this program introduces project-based learning methods and the use of technology in education. The results show a significant increase in the use of scientific writing methods and students' confidence in writing. Positive impacts can also be seen in student involvement and motivation in scientific writing training. The program is innovative in its integration of digital technology and collaborative approach between academics and aspiring academics. Based on the results, it is recommended to implement similar programs in other universities with varied contexts. This program highlights the importance of new student training in developing the quality of scientific writing education and preparing students for a competitive future